1990
DOI: 10.1016/0014-5793(90)81237-i
|View full text |Cite
|
Sign up to set email alerts
|

Immunological detection of the mitochondrial F1‐ATPase α subunit in the matrix of rat liver peroxisomes

Abstract: Rat liver peroxisomes contain in their matrix the a-subunit of the mitochondrial F,-ATPase complex. The identification of this protein in liver peroxisomes has been achieved by immunoelectron microscopy and subcellular fractionation. No /?-subunit of the mitochondrial F,-ATPase complex was detected in the peroxisomal fractions obtained in sucrose gradients or in Nycodenz pelletkd peroxisomes. The consensus peroxisomal targeting sequence (Ala-Lys-Leu) is found at the carboxy terminus of the mature cc-subunit fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

1991
1991
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…While the role of molecular chaperones in mitochondrial biogenesis has been partially elucidated during the last few years (see above), nothing is yet known about the existence of a proteinaceous machinery in the peroxisomal matrix that could perform similar functions to those reported for mitochondrial molecular chaperones. However, results from our laboratory initially suggested that a chaperonin function in the peroxisomal matrix could be partially accomplished by the major regulatory subunit (o~-subunit) of the mitochondrial F-type ATPase (ca 57-kDa protein) [31,33,107].…”
Section: Peroxisomal Chaperones and Chaperonins?mentioning
confidence: 99%
See 2 more Smart Citations
“…While the role of molecular chaperones in mitochondrial biogenesis has been partially elucidated during the last few years (see above), nothing is yet known about the existence of a proteinaceous machinery in the peroxisomal matrix that could perform similar functions to those reported for mitochondrial molecular chaperones. However, results from our laboratory initially suggested that a chaperonin function in the peroxisomal matrix could be partially accomplished by the major regulatory subunit (o~-subunit) of the mitochondrial F-type ATPase (ca 57-kDa protein) [31,33,107].…”
Section: Peroxisomal Chaperones and Chaperonins?mentioning
confidence: 99%
“…Based on the immunoreactivity towards a rabbit anti-(rat liver mitochondrial FrATPase complex) serum [176], the mitochondrial F~-ATPase ~-subunit was shown to be present also in the matrix of rat liver peroxisomes [31]. This was assessed both by immunoelectron microscopy of rat liver thin sections, in which a highly specific immunolabeling of mitochondria and peroxisomes could be observed [31,33], and by Western blotting fractionated peroxisomal and mitochondrial proteins [31]. In addition, it was shown that bovine and rat liver FrATPase ~subunit sequences contain a typical carboxy-terminai type II peroxisomal targeting signal [31,33].…”
Section: Peroxisomal Chaperones and Chaperonins?mentioning
confidence: 99%
See 1 more Smart Citation
“…Some mitochondria were likely isolated with the nuclear fraction in both experiments as evidenced by the presence of an α and a β polypeptide of the F1 part of ATP synthase (table 1). ATP synthases are mitochondrial proteins although they have been identified in peroxisomes [21] and in the plasma membrane [22]. We did not identify other mitochondrial proteins that would lend support to the view that there was contamination.…”
Section: Discussionmentioning
confidence: 48%
“…A similar distribution has been described for the ␣ subunit of the F 1 -ATPase (46). In the context of a possible transduction of a Ca 2ϩ signal to the inside of peroxisomes and mitochondria this could lead to coordinated action of both organelles.…”
Section: Discussionmentioning
confidence: 72%